Maintainability Prediction of EMUs Traction Inverter - SHAO Zhi-he; CHEN Le-sheng; CHENXu-hong; LIAO Min-feng (机车电传动)
Basic maintainability prediction methods were introduced, function diagram and mathematical model of which was built by taking EMUs traction inverter as example. Time accumulation method was used to predict the maintainability level, the maintainability prediction results was analyzed to find the weak links in maintainability design, which provided reference for traction inverter maintainability design.